If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/3(x+1)=1/2(x-2)
We move all terms to the left:
1/3(x+1)-(1/2(x-2))=0
Domain of the equation: 3(x+1)!=0
x∈R
Domain of the equation: 2(x-2))!=0We calculate fractions
x∈R
(2xx/(3(x+1)*2(x-2)))+(-3xx/(3(x+1)*2(x-2)))=0
We calculate terms in parentheses: +(2xx/(3(x+1)*2(x-2))), so:
2xx/(3(x+1)*2(x-2))
We multiply all the terms by the denominator
2xx
Back to the equation:
+(2xx)
We calculate terms in parentheses: +(-3xx/(3(x+1)*2(x-2))), so:We get rid of parentheses
-3xx/(3(x+1)*2(x-2))
We multiply all the terms by the denominator
-3xx
Back to the equation:
+(-3xx)
2xx-3xx=0
| 19+7y=5 | | 4+c15=-9 | | 8+(x-6)=-2=+2x-2 | | 7+2x=1-2x | | 2x=2235-5x | | 90+.6x=60+.90x | | 3x+76=144 | | 8-v=19 | | |x|=1.4 | | (12-3x)^3=0 | | A/10-3a/20=5/4-3a/10 | | 3(x+14)=27 | | 60/64=x/48 | | 1.6×n=6.4 | | 3x-7=11x-15 | | -2v+7=1+3v-6v | | X/12=1/3-x/12 | | 90=-18v | | -8v+6(v+7)=38 | | 9(x-1)-8=5x+4(-3+x) | | 9(x-1)-8=5x+4(-3+x | | -102-2x=-7 | | 2(3b+6)=-(8-4b) | | 4k=1.5k+50 | | 4x+5x+6=10 | | F(x)=15+2x^2 | | -39+3v=5(v-5) | | 5b-4-4=7b+8 | | −2(3z+1)−10=4−2(3z+1)−10=4 | | F(-4)=12-3x | | 3x=−21 | | (4x+1)+(5x-6)=76 |